2012
DOI: 10.1104/pp.112.200824
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Xylem Sap from Functional (Nonembolized) and Nonfunctional (Embolized) Vessels of Populus nigra: Chemistry of Refilling      

Abstract: It is assumed that the refilling of drought-induced embolism requires the creation of an osmotic gradient between xylem parenchyma cells and vessel lumens to generate the water efflux needed to fill the void. To assess the mechanism of embolism repair, it is crucial to determine if plants can up-regulate the efflux of osmotically active substances into embolized vessels and identify the major components of the released osmoticum. Here, we introduce a new approach of sap collection designed to separate water fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 50 publications
9
115
0
Order By: Relevance
“…2 and 4, B and C). According to refilling models for angiosperms (Nardini et al, 2011), starch may be degraded to osmotically active sugars, which are released into embolized conduits thereby creating a driving force for water inflow (Bucci et al, 2003;Secchi and Zwieniecki, 2012). Observed starch accumulation in phloem and needle tissues may thus be required to provide sufficient osmotica for local changes in C. Interestingly, we found no significant seasonal changes in Glc or Fru (data not shown).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…2 and 4, B and C). According to refilling models for angiosperms (Nardini et al, 2011), starch may be degraded to osmotically active sugars, which are released into embolized conduits thereby creating a driving force for water inflow (Bucci et al, 2003;Secchi and Zwieniecki, 2012). Observed starch accumulation in phloem and needle tissues may thus be required to provide sufficient osmotica for local changes in C. Interestingly, we found no significant seasonal changes in Glc or Fru (data not shown).…”
Section: Discussionmentioning
confidence: 43%
“…Because osmotica have to be released only into refilling tracheids, variations in sugar concentrations probably occur on a small spatial scale and thus cannot be detected by analysis of entire tissue samples. In Populus, a special method enabled the analysis of sugar contents in embolized and intact vessels (Secchi and Zwieniecki, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2). In this scenario, starch degradation appears to play a key role in providing the osmotica (Salleo et al 2004;Secchi and Zwieniecki 2012), while aquaporins are required to reduce hydraulic resistance along the symplastic pathway . Phloem transport has also been demonstrated to be involved in embolism reversal, as different studies showed that phloem girdling inhibits the process (Salleo et al 2004;Nardini et al 2014).…”
Section: Recent Non-destructive Methodsmentioning
confidence: 99%
“…Refilling conduits have more negative osmotic potential than still functioning ones (Secchi and Zwieniecki 2012). In a hypothetical scenario that found partial experimental confirmation, drought-induced rise in abscisic acid (ABA) concentration would lead to upregulation of several genes in vessel-associated parenchyma, including those coding for aquaporins and enzymes related to carbohydrate metabolism and starch degradation (Secchi and Zwieniecki 2010).…”
Section: Processesmentioning
confidence: 99%
“…The mechanisms involved in refilling without tension are still under debate (see Zwieniecki and Holbrook (2009) and Brodersen and McElrone (2013) for a detailed review). However, there is strong evidence that sugars derived from starch polymerisation in xylem parenchyma generate an osmotic gradient that then drives water inflow from adjacent parenchyma cells into conduits (Salleo et al 2004;Zwieniecki and Holbrook 2009;Nardini et al 2011;Secchi and Zwieniecki 2012). Two important prerequisites therefore are: (I) adequate water supply, with living cells in the xylem and phloem potentially playing a major role (Salleo et al 2004;Brodersen et al 2010;Nardini et al 2011); (II) hydraulic isolation of embolised conduits from water-filled conduits under tension.…”
Section: Introductionmentioning
confidence: 99%